Character Education Values in Traditional Malay Songs - Lubis, Maya Ningsih; Sunarto, Sunarto; Sinaga, Syahrul Syah; Nugrahani, Rahina (Journal La Edusci, 2025)
Character Education is important in facing global challenges. The moral crisis that causes the young generation to lose their identity due to the influence of foreign culture makes character education important. This research focuses on the lyrics of traditional Malay songs that instill the values of character education. Traditional Malay songs that contain character education values are titled Timang Cenggok and Iyolah Molek. This study uses a qualitative design with a phenomenological approach. The research location is in North Sumatra. Researchers collected data by means of observation, interviews and document collection. The results of the study found that traditional Malay songs entitled Timang Cenggok and Iyolah Molek instill religious values, discipline, responsibility and independence. The religious character in traditional Malay songs directs obedience to religious commands. The character of discipline in traditional Malay songs leads to an attitude of perseverance in carrying out a job or task. The character of responsibility in traditional Malay songs leads to the importance of responsibility at work. The independent character in traditional Malay songs leads to the importance of an independent person and not doubting oneself.